Performance of serial acquirers: toward an acquisition program perspective - Laamanen, Tomi; Keil, Thomas (Strategic Management Journal, 2008)
Abstract Based on an analysis of the most active acquirers in seven industry sectors in the United States in the 1990s, we find that both a high rate of acquisitions and a high variability of the rate are negatively related to performance. An acquirer's size, the scope of its acquisition program, and acquisition experience moderate the relationship by weakening the negative effects. Our findings contribute to an improved understanding of acquisition capabilities and program‐level acquisition performance, thereby adding to an emerging stream of research that is building an acquisition program perspective. Copyright © 2008 John Wiley & Sons, Ltd.